Seasonal Occurrence of the Polychaete Worm Namalycastis indica and its Ability to Accumulate Heavy Metals in the Shatt Al-Basrah Canal - Al-Baghdadi, Nada (Iraqi Journal of Aquaculture, 2025)
The worm Namalycastis indica is a Polychaete that lives in the intertidal zone under rocks and is tolerant of fluctuating conditions, especially temperature, salinity, and exposure to pollutants, and contributes to the balance of the aquatic ecosystem. This research aims to study the seasonal presence and density of N. indica in the Shatt al-Basra Regulator habitat, calculate the concentrations of heavy metals in their bodies and in the intertidal zone sediments, determine the bioaccumulation factor (BAF) of the worms and the sediments and the relationship between BAF and the environmental factors, and their relationship to the distribution of the worms. The total density (individual/m²) of individuals was identified collected using a 0.25m x 0.25m square frame for quantitative sampling. The highest average density of the species was recorded at 112 individuals per square meter during the spring season, and the lowest average density was 32 during the summer season. The results showed variation in environmental factors between seasons, water temperature ranged between 15.2-33.1˚C. Higher value of salinity recorded in summer season was 43.7‰. Dissolved oxygen ranged between 5.8-8.7 mg/l, and pH between 7.3-7.6. The results also showed that worm length average ranged between 4.7-7.16 cm. four were measured, heavy metals: Cobalt, nickel, cadmium, copper, The results of heavy metals for worms bodies showed arrangements from high to low concentrations during all study periods as follow: Co > Ni > Cd > Cu for N. indica tissues and Ni > Co> Cu >Cd in sediment.